2019
DOI: 10.1108/jhr-11-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life of the rural older adults in Northern Thailand

Abstract: Purpose The purpose of this paper to explore socio-demographic factors related to the quality of life (QoL) among older adults in the rural area of Thailand. Design/methodology/approach This cross-sectional study examined socio-demographic factor that may predict the QoL among 470 older adults who lived in a rural area of Northern Thailand. The study questionnaire consisted of four parts, including socio-demographic data, perceptions of the health status, family relationship and QoL (WHOQOL-OLD). Spearman’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
2
10
0
4
Order By: Relevance
“…Self-care decreases when people enter the aging process and heavily rely upon others for daily activities, thus decreasing the QOL. This study suggests that the younger have 11.07 times higher QOL than older age groups, which is similar to the results from previous studies reporting that older adults had low QOL [10,32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Self-care decreases when people enter the aging process and heavily rely upon others for daily activities, thus decreasing the QOL. This study suggests that the younger have 11.07 times higher QOL than older age groups, which is similar to the results from previous studies reporting that older adults had low QOL [10,32].…”
Section: Discussionsupporting
confidence: 91%
“…Health professionals from 22 countries applied and validated the tool among the elderly [4]. Currently, this tool is used to measure QOL in numerous studies globally [5][6][7][8][9][10][11][12]. Previous studies noted that the survival rates of older people have increased; however, the quality of life (QOL) is substantially low.…”
Section: Introductionmentioning
confidence: 99%
“…Divorced people can also experience higher pressure and stress than married or single people, as Conversano et al reported that living with a spouse resulted in lower distress during the COVID-19 pandemic [ 42 ]. However, the impact of marital status on the QoL in different societies is partly influenced by their cultural and social conditions, as Seangpraw et al [ 43 ] could not find this result among the rural older adults in Northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Creating suitable jobs for older adults who can still work may be needed along with connecting the elderly who can no longer work to family or community resources. In term of educational level, older employees with a higher level of education had more advantages [35]. They may have superior living conditions, fewer chance of being exposed to risk factors of diseases, less labor-intensive work, a network of friends and a higher sense of self potency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Creative workshops or short-term training (i.e. painting, basketry, massage and herbal gardening) may also contribute additional income for older elders [35].…”
Section: Literature Reviewmentioning
confidence: 99%